202k views
5 votes
Which expressions are equivalent to 4m-2+(-8m)?

User Toprak
by
5.2k points

2 Answers

3 votes

Answer:

A and B

I got it right on khan :)

Explanation:

User Compuguru
by
5.5k points
1 vote

Answer:

The equivalent expression to the given expression 4m-2+(-8m) is -2(2m+1)

That is 4m-2+(-8m)=-2(2m+1)

Explanation:

The given expression is 4m-2+(-8m)

To find the equivalent expression to the given expression 4m-2+(-8m):

4m-2+(-8m)=4m-2-8m ( here using Associative property )

=-4m-2 ( adding the like terms )

=-2(2m+1) ( taking common term -2 in the above expression )

Therefore 4m-2+(-8m)=-2(2m+1)

Therefore The equivalent expression to the given expression 4m-2+(-8m) is -2(2m+1)

That is 4m-2+(-8m)=-2(2m+1)

User DrkStr
by
4.9k points